Relaxation and tunnelling of structural units within the LTO phase of La2CuO4 - Cannelli, G.; Cantelli, R.; Cordero, F.; Grandini, Carlos Roberto [UNESP] (Editrice Compositori Bologna, 1998)
The anelastic relaxation (elastic energy loss and Young modulus) of nearly stoichiometric La2CuO4+delta with LTO structure was measured. Extraordinarily intense effects are present below room temperature in the elastic dynamic susceptibility, indicating relaxational dynamics of a relevant fraction of the lattice. The involved degrees of freedom are identified as rotations of the CuO6 octahedra. Two distinct processes are found at frequencies around 1 kKz: one is observed around 150 K and is characterized by a mean activation energy of 2800 K; the second one occurs below 30 K and is governed by atomic tunnelling. Two explanations are proposed for the faster process: i) formation of fluctuating LTT domains on a scale of few atomic cells; ii) the LTO phase is a dynamical Jahn-Teller phase with all the octahedra tunneling between two LTT-like tilts. In both cases there would be important implications regarding the mechanisms giving rise to charge nanophase separation and strong electron-phonon coupling.